Retooling Technology; Recasting Creativity. - Brown, Glen R. (Ceramics: Art & Perception, 2010)
The article presents information on the ceramic sculptures made by Philadelphia, Pennsylvania-based sculptor Chad Curtis. He incorporated computer-aided technologies with his sculptures and drawings. Curtis's sculpture titled "Cows" is made of ceramic clay which features orange and green bovines on top of a curvaceous, bubblegum-pink pasture. His "Popup Camper with Tree" sculpture is made of glazed ceramic which features an orange camper besides a pink pine that matches the color of a pink plateau.